Row Covers for Commercial Vegetable Culture in Florida - George J. Hochmuth; Robert C. Hochmuth; Steve Kostewicz; William Stall (EDIS)
This publication describes the present state of technology regarding row covers in the United States and provides examples of potential applications of that technology to Florida vegetable production. This document is CIR728, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date July 1987. Reviewed March 2015. Revised September 2018.